Methods for Evaluating Immersive 3D Virtual Environments: a Systematic Literature Review - Peres, Fabiana Frata Furlan; Nunes, Fatima; Teixeira, João Marcelo; Maurício, Claudio R. M.; Conceição, Katiani P.; Yoshida, Leina (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Although evaluation methods for Virtual Reality systems have been proposed in many studies, most of them are developed for particular applications with no possibility of generalization. Additionally, few studies proposed compilation and categorization of these studies, which turn difficulty obtaining an overview of the state-of-art. This systematic literature review aims to analyze and categorize evaluation methods for interaction in immersive three-dimensional virtual environments. By reviewing studies published from 2019 to April 2024, diverse approaches and methodologies used to assess Virtual Reality interaction techniques were identified. The studies were categorized into five main areas: locomotion, input, visualization and selection, evaluation of haptic interfaces, and transitions and scenarios. Our findings highlight that most studies employed established evaluation methods, with only one study proposing new method. Objective method, particularly time-related measures, were frequently used, alongside subjective method obtained through questionnaires and interviews. The review emphasizes the importance of combining subjective and objective method to provide a comprehensive analysis of user experience and interaction effectiveness. A significant need for standardized evaluation frameworks to enable consistent comparisons across studies was identified.